2017
DOI: 10.3892/ijo.2017.3934
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine sensitizes chronic myeloid leukemia cells to Vγ9Vδ2 T cell-mediated lysis independent of autophagy

Abstract: Hydroxychloroquine (HCQ) is the only autophagy inhibitor in clinical use and it has shown great potential in treating chronic myeloid leukemia (CML). By inhibiting autophagy, HCQ enhances the anti-CML efficiency of chemotherapy. In the present study, we demonstrated that HCQ sensitized CML cells to Vγ9Vδ2 T cell-mediated lysis. HCQ inhibited autophagy in CML cells, but the sensitizing effects of HCQ were autophagy-independent. Since the sensitization was not mimicked by ATG7 knockdown and even occurred in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
(80 reference statements)
0
3
0
Order By: Relevance
“…Assessing abundance of ULBP4 transcripts in a broad variety of human tumor cell lines, we detected ULBP4 transcripts most abundantly in the cervix carcinoma cell line HeLa, whereas ULBP4 transcripts were undetectable in liver cancer cells HepG2 or in the erythroleukemia line K562 (Figure 4 B and data not shown) well in line with publicly available data sets. 4 Of note, pronounced ULBP4 surface expression has been claimed based on binding of mAb 709116 for HepG2 cells by the supplier, 5 for the erythroleukemia line K562 ( 42 ) and for cytokine-activated NK cells ( 32 ). By using DUMO1 and ULBP4-specific pAb, we were unable to detect ULBP4 surface expression on HeLa, HepG2, HCT116, and HaCat cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Assessing abundance of ULBP4 transcripts in a broad variety of human tumor cell lines, we detected ULBP4 transcripts most abundantly in the cervix carcinoma cell line HeLa, whereas ULBP4 transcripts were undetectable in liver cancer cells HepG2 or in the erythroleukemia line K562 (Figure 4 B and data not shown) well in line with publicly available data sets. 4 Of note, pronounced ULBP4 surface expression has been claimed based on binding of mAb 709116 for HepG2 cells by the supplier, 5 for the erythroleukemia line K562 ( 42 ) and for cytokine-activated NK cells ( 32 ). By using DUMO1 and ULBP4-specific pAb, we were unable to detect ULBP4 surface expression on HeLa, HepG2, HCT116, and HaCat cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been established that Vδ1 and Vδ2 cells can destroy ULBP2 + LCs ( 133 ). Although an almost undetectable ULBP4 expression has been reported in leukemias ( 129 , 134 ), remarkably, it has been shown that Vδ2 cells detect this molecule in LCs and respond with potent cytotoxicity ( 135 ). Therefore, the NKG2D receptor plays a key-role in γδ T cell-mediated immune surveillance in leukemia.…”
Section: γδ T Cells and Leukemia: The Leukemic Microenvironment Mattersmentioning
confidence: 99%
“… 96 , 97 While cancer cells may secrete immunosuppressive mediators to inhibit T cells’ cytotoxicity, both ART and ARS help cancer cells regain sensitivity to γδ T cells via inhibiting TGF-b secretion. 97 , 101 These results suggested that ARTs may help construct a more stressful microenvironment for cancer cells, and its potential application in cancer-related immune regulation is worth of exploring in the future.…”
Section: Immunoregulating Effect Of Antiparasitic Agentsmentioning
confidence: 93%